Practices of Pre-service Science Teacher Education Program: Review and Reflection - Koirala, Kamal Prasad (The Educator Journal, 2022)
This paper aims to examine the effectiveness of the pre-service teacher practicum program of M. Ed level from the perspective of the campus supervisor of Gorkha Campus, Gorkha. There were altogether six students who appeared in the practicum program, and the researcher was their internal mentor for them. The teaching practice (practicum) program was conducted for about two months in six phases (four on-campus and two in cooperative schools). Based on peer observation and researcher observation analysis for each student-teacher classroom, five findings were identified and interpreted as Technological Pedagogical and Content Knowledge (TPACK) and related other theories. The analysis indicated that the theoretical, pedagogical knowledge was not much implemented in teaching. Their teaching was more traditional without ICT except for on-campus teaching practice. The obtained pedagogical and content knowledge was not tried to link their teaching with life-world knowledge, except a few student teachers did so. The pedagogical skills mentioned in the peer observation form were not developed fully even after the completion of the theory classes and the end of teaching practice. The critical scientific thinking (SCT) model is new and may be appropriate for the practicum program. This teaching practicum program was insufficient to fill the theory-practice gap using this model.